Pengaruh FCF, IOI & DER terhadap DPR Sub Sektor Logam dan Sejenisnya di Bursa Efek Indonesia - Melati Dia Kusuma; Umi Nadhiroh; Udik Jatmiko (Pusat Riset dan Inovasi Nasional, 2022)
Investors invest their capital in a metal and allied company expecting the return of shares from the investment results, either in the form of dividends or capital gains. The purpose of this study is to determine the independent variables of free cash flow, investment opportunity set, and debt to equity ratio on the dependent variable of dividend payout ratio in metal and allied product companies listed on the Indonesia Stock Exchange in 2016-2020. The population in this study is the metal and similar sub-sector companies on the Indonesia Stock Exchange, totaling 17 companies, and the selected sample is 6 companies because they have met the criteria for purposive sampling. Using secondary data as research data obtained from the annual financial statements of metal and allied product sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020 with the analytical technique used is panel data regression analysis with the help of Eviews 10 software. The results of this study indicate that the free cash flow variable, the investment opportunity set partially has a negative and insignificant effect on the dividend payout ratio, and the debt to equity ratio variable partially has a positive and insignificant effect on the dividend payout ratio. Simultaneously free cash flow, investment opportunity set, and debt to equity ratio have no significant effect on the dividend payout ratio